Age- and gender-associated variation in maximal-intensity exercise performance in adolescent rowers - Mikulic, P.; Markovic, G. (International Journal of Sports Medicine, 2011)
We aimed to (1) characterize the 30-s maximal-intensity exercise performance using a Wingate rowing test in 12- to 18-year-old female rowers grouped by age, and (2) to compare the obtained performance indicators (i. e., mean- and maximal power output) with those of male rowers (n=297) of the same age. 193 female rowers (mean±SD: 14.9±1.9 years; range: 12.0-18.9 years) completed a maximal 30-s test on a rowing ergometer. An ANOVA with Bonferroni post-hoc analyses was used to compare the performances among the age groups, and age-related increases in performance up to age 15 with a plateau in performance thereafter, were observed. The age-related increases in performance were reduced by approximately one half when the effects of body mass were statistically removed with the use of ANCOVA. Gender-associated differences in Wingate rowing test performance were observed from age 13 (p<0.05, +19-22% in favour of males) and increased thereafter. Between the ages of 16 and 18, these differences appeared to change very little and ranged between ?50-60% (all p<0.001). This pattern of gender-associated differences was similar, although the differences were reduced in relative terms by about one third, when the body mass of rowers of both sexes was statistically removed using ANCOVA analyses.